Head Teacher’s Self-efficacy with Transforming Leadership for Changing School - Adhikari, Devi Prasad (The EFFORTS, Journal of Education and Research, 2024)
In the context of Nepal, most of government-aided schools are poorly managed. They could not provide good achievement academically and non-academically. Head teacher's leadership is considered highly significant for the transformation of such schools. The schools are not getting expected change. However, there are very few schools that have been transformed considerably. This study explored the role of head teachers’ self-efficacy and their transformative leadership qualities in connection to the transformation of schools. Along with this, teachers' perception about the head teachers' leadership role and impact in the transformation process were also underpinned. This multiple case study of two government schools from Dhading district adopted qualitative method. The findings were illustrated in narrative and descriptive way. Research findings indicated the current situation of transformed schools, leadership effect, the head teachers' self-efficacy and transformative leadership qualities. The findings are helpful to head teachers, administrators, teachers, policy makers and school managers per se in order to transform schools.